KEBERADAAN KOMUNITAS MEDAN DRUMMER FOUNDATION DI KOTA MEDAN - Ryanda Shatria Mandala Lubis (Universitas Negeri Medan, 2013)
The results of this study based on the data collected, the researcher can conclude that this community was formed with the aim of develop the skills of drummer in Medan that still play by way of self-taught by means of routine educational activities such as Coaching clinic and Master Class. But this educational activity will not be fulfilled if it is not supported by the means and supporting infrastructure that comes from sponsorship, Raja Music and Sonor drums. With the support that has been given by the Raja Music and Sonor drums, it was enough to help the Medan Drummer Foundation Community to further develop its presence. It all proved of positive responses from the community or audience about how the development of this community from the beginning formed until right now.